Growth patterns of the airway in Crouzon syndrome patients with different types of cranial vault suture synostosis. Issue 7 (July 2021) - Lu, X.; Forte, A.J.; Wilson, A.; Park, K.E.; Allam, O.; Alperovich, M.; Steinbacher, D.M.; Tonello, C.; Alonso, N.; Persing, J.A.
Abstract: The severity of obstructive respiratory difficulty varies among affected Crouzon syndrome patients. The aim of this study was to investigate the correlation between the restricted airway volume in Crouzon syndrome and the associated type of cranial vault suture synostosis. Computed tomography scans of 68 unoperated Crouzon syndrome patients and 89 control subjects were subgrouped into four types: type I, bilateral coronal synostosis; type II, sagittal synostosis; type III, pansynostosis; type IV, perpendicular combinations of synostoses. Measurements were made using Mimics software. Of type I Crouzon patients, 42% had a restricted nasal airway ( P  = 0.002), while the pharyngeal airway volume was not significantly reduced. Type II Crouzon patients grew normal segmental airway volumes. Crouzon patients of type III developed simultaneously reduced nasal and pharyngeal airway volumes in infancy, by 38% ( P  = 0.034) and 51% ( P  = 0.014), respectively. However, the nasal airway achieved a normal volume by 2 years of age without any intervention, while the pharyngeal airway remained significantly reduced up to 6 years of age, by 42% ( P  = 0.013), compared to controls. Type IV Crouzon patients developed a reduced nasal airway volume (32%, P  = 0.048) and a non-significant restricted pharyngeal airway (18%, P  = 0.325). Airway compromise in Crouzon syndrome is variable when associated with different craniosynostosis fusion patterns. Type II (sagittal synostosis) Crouzon patients grew a normal nasopharyngeal airway volume. Those with types I (bicoronal synostosis) and IV (perpendicular synostoses) had significantly restricted nasal airways and a tendency towards a reduced pharyngeal volume. Type III (pansynostosis) Crouzon infants had the worst restriction of both airways, although there was some improvement with age.